Observed Anomaly of Temperature and Mixed Layer Depth Associated with the Madden Julian Oscillation (MJO) Active Phase in the Banda Sea, Indonesia - Nabil, Nabil; Atmadipoera, Agus Saleh; Nugroho, Dwiyoga; Naulita, Yuli; Koch-Larrouy, Ariane (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
The eastward propagation of atmospheric waves along the equatorial band from the central equatorial Indian Ocean to the western Pacific Ocean passing through the Indonesian Maritime Continent (IMC), known as the intraseasonal Madden Julian Oscillation (MJO) event, plays an important role on modulating both atmospheric and upper ocean dynamics along its path. This study aims to investigate the MJO active phase dynamics and its impact on changes in near-surface seawater temperature and mixed layer depth (MLD) anomaly in the Banda Sea Indonesia, using multi-datasets of atmospheric reanalysis, satellites derived sea surface temperature (SST), and Argo float between 2017 - 2018. This study revealed that the MJO waves propagate eastward along the southern equator-line over the IMC and pass through the Banda Sea, associated with significant decreased on Outgoing Longwave Radiation (OLR) and increased in zonal wind speed at 850hPa. The study result shows anomalous increased on surface wind speed and SST cooling during of MJO active phase. The amplitude peaks of filtered ocean-atmosphere variables range between 30 – 60 days. Argo float datasets in the Banda Sea for the first time captured upper ocean responses to the arrival of the MJO active phase, as characterized by a negative temperature anomaly of ~0.3°C in the surface mixed layer, large temperature anomaly of ~0.8°C in the thermocline layer and the deepening of the MLD of ~25 m. Hence, the MJO active phase impacts significantly on surface and vertical temperature cooling and regulate upper ocean mixing intensity in the Banda Sea.